2004
DOI: 10.1074/jbc.m313072200
|View full text |Cite
|
Sign up to set email alerts
|

Dual Function of Interleukin-1β for the Regulation of Interleukin-6-induced Suppressor of Cytokine Signaling 3 Expression

Abstract: Interleukin-6 (IL-6) exerts pro-as well as anti-inflammatory activities in response to infection, injury, or other stimuli that affect the homeostasis of the organism. IL-6-induced expression of acute-phase protein genes in the liver is tightly regulated through both IL-6-induced feedback inhibitors and the activity of proinflammatory cytokines such as tumor necrosis factor ␣ and interleukin-1␤. In previous studies mechanisms for how

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 38 publications
(43 reference statements)
2
20
0
Order By: Relevance
“…The results indicated that the activation of p50-p65 and the B site at Ϫ69, contributed only partially to the synergistic effect of IL-1 on IL-6-induced CRP gene expression. Our data support the idea that IL-1, besides activating NF-B in Hep3B cells, participates in IL-6 synergy via other pathways, as has been shown in the case of other IL-1-regulated genes (29).…”
Section: Discussionsupporting
confidence: 90%
“…The results indicated that the activation of p50-p65 and the B site at Ϫ69, contributed only partially to the synergistic effect of IL-1 on IL-6-induced CRP gene expression. Our data support the idea that IL-1, besides activating NF-B in Hep3B cells, participates in IL-6 synergy via other pathways, as has been shown in the case of other IL-1-regulated genes (29).…”
Section: Discussionsupporting
confidence: 90%
“…S1 for quantification). We recently reported that IL1b enhances IL-6-induced SOCS3 expression by stabilising SOCS3 mRNA (Yang et al, 2004). However, we could show that IL-1b was able to inhibit IL-6-mediated STAT3 activation independent of de novo protein synthesis (Fig.…”
Section: Il-1b Negatively Regulates Stat Activation By Il-6-type Cytomentioning
confidence: 79%
“…These cells have been extensively characterised and lack NF-kB activation in response to IL-1b [ Fig. 1C, compare lanes 1-5 with lanes 6-10 and Yang et al (Yang et al, 2004)]. Fig.…”
Section: Il-1b Negatively Regulates Stat Activation By Il-6-type Cytomentioning
confidence: 97%
See 1 more Smart Citation
“…Although IL-6-induced STAT-3 phosphorylation was reduced to ϳ70% by IL-1␤ in the absence of SB202190, pretreatment with this inhibitor efficiently blocked the inhibitory effect of IL-1␤ ( Figure 4B). It has previously been shown that proinflammatory cytokines such as TNF␣ and IL-1␤ can enhance IL-6-induced feedback via SOCS-3 by stabilizing SOCS-3 mRNA (20,21). Therefore we investigated whether IL-1␤ could reduce IL-6-induced STAT-3 activation independent of de novo protein synthesis and, thus, SOCS-3 expression.…”
Section: Honke Et Almentioning
confidence: 97%